Pengaruh Profitabilitas, Likuiditas, dan Ukuran Bank Terhadap Struktur Modal Pada Industri Perbankan di Bursa Efek Indonesia - Lambok Nababan (University of Merdeka Malang, 2023)
This research is motivated by the gap phenomenon about capital structure and the inconsistency of previous research results. The purpose of this research is to determine the effect of profitability, liquidity, and bank size on capital structure in the banking industry listed on the Indonesia Stock Exchange in 2019-2022. This type of research is quantitative descriptive research. This research was conducted in the banking industry that has been listed on the Indonesia Stock Exchange in the 2019-2022 period with a saturated sampling method or pooled sampling where this method is a way of sampling where all members in the population are used as samples. This study uses secondary data and the analysis tool used is SPSS software. The results of this study found that profitability and bank size variables have a significant effect on capital structure while liquidity variables have a negative effect on capital structure in the banking industry in Indonesia. The results of this study are also expected to be a reference for further research to increase the number of research variables and increase the number of research populations in various sectors and increase the research period.